The Effect of Organizational Culture on Employee Retention Through Affective Commitment as an Intervening Variable in The Cooperative, Small and Medium Enterprises, Industry, and Trade Office of Southwest Papua Province - Darmawaty Syam; Winarsih Winarsih; Jullie J. Sondakh; Hendra N. Tawas; Agus Supandi Soegoto; Hizkia Hendrik David Tasik (Maneggio, 2025)
This study aims to examine the effect of organizational culture on employee retention with affective commitment as an intervening variable at the Office of Cooperatives, Small and Medium Enterprises, Industry, and Trade of Southwest Papua Province. A quantitative approach was employed using a census method involving 87 employees, and the data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) through SmartPLS software. The results indicate that organizational culture has a positive and significant effect on affective commitment and employee retention. Furthermore, affective commitment is proven to partially mediate the relationship between organizational culture and employee retention. These findings suggest that employees’ emotional attachment serves as a key psychological mechanism linking the internalization of organizational cultural values to retention decisions. From a theoretical perspective, this study contributes to public human resource management literature by empirically validating the mediating role of affective commitment within newly established autonomous regional governments. Practically, the findings offer policy-relevant insights for local governments by demonstrating that strengthening organizational culture and emotional attachment can function as effective non-financial human resource management strategies to enhance employee retention and workforce stability in transitional public sector institutions.